Method for preparing phosphate fertilizer from iron phosphate slag obtained after lithium extraction of waste lithium iron phosphate

By reacting the iron phosphate slag in waste lithium iron phosphate batteries with soda ash, it transforms it into sodium phosphate fertilizer, and solves the problem of incomplete recovery of phosphorus resources, achieving efficient and low-cost production of phosphorus fertilizers, which is suitable for large-scale industrial recycling and agricultural use. .

CN119263893APending Publication Date: 2025-01-07SUZHOU LIDAO SHUYUAN NEW ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411639442.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When recycling lithium iron phosphate batteries in the prior art, there are problems such as incomplete recovery of phosphorus resources, high energy consumption, high cost, complex process, and only partial raw materials can be used, and large-scale industrial production cannot be achieved.

Method used

A method of making phosphate fertilizer by removing waste lithium iron phosphate lithium, is used to react iron phosphate slag with soda ash, convert iron phosphate into soluble sodium phosphate, and then use sulfuric acid to adjust the pH value to make phosphate fertilizer, which is suitable for large-scale industrialization Recycle.

Benefits of technology

It realizes short-process, simple and efficient phosphorus source recycling, which is suitable for large-scale industrialization, and converts waste lithium iron phosphate slag into fertilizers that can be used in agriculture, reducing environmental pollution and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263893A_ABST
    Figure CN119263893A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a phosphate fertilizer from iron phosphate slag obtained after lithium extraction of waste lithium iron phosphate. The method comprises the following steps: step a, mixing waste lithium iron phosphate powder with water according to a certain proportion to obtain slurry; b, free water and crystal water are removed from the iron phosphate slag; c, the soda ash is subjected to pulping to obtain alkali liquor; step d, fully and uniformly mixing the iron phosphate slag with alkali liquor to obtain a mixture; step e, continuously stirring the mixture for a certain time; f, heating the mixture; step g, sampling, and respectively detecting the contents of available phosphorus and water-soluble phosphorus; step h, adding sulfuric acid into the qualified reactants of available phosphorus and water-soluble phosphorus in a spraying manner; step i, drying and dehydrating the reactant to obtain a material; and step j, adding an adhesive into the material to obtain the powdery fertilizer. According to the invention, phosphorus is comprehensively utilized in the form of phosphate fertilizer while lithium in the waste material of the lithium iron phosphate battery is recycled, so that comprehensive recycling of resources is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery material recycling, and in particular to a method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate. Background Art

[0002] Lithium-ion batteries have become an indispensable energy storage device in today's society. Due to its green and environmentally friendly nature, low environmental pollution, and excellent electrochemical properties, lithium iron phosphate is currently the most widely used lithium-ion battery material. It is regarded by many people in the industry as the future development direction of lithium batteries and has been widely used in various fields of life. At present, my country is undergoing iterative updates in the automotive industry, the rapid development of new energy vehicles, and the expansion of 5G base stations. Due to its high operating voltage, high energy density, long cycle life, good safety performance, low self-discharge rate, and no memory effect, its market share has increased year by year. However, half of the life of lithium iron phosphate batteries is 5-8 years, which will produce a large number of waste lithium iron phosphate batteries, causing great environmental pressure. At the same time, the valuable metals in waste lithium iron phosphate batteries have a high recycling value, and recycling them has huge social and economic benefits.

[0003] With the explosive development of the lithium battery new energy market, the problem of handling waste lithium iron phosphate batteries has become increasingly prominent. 4 The waste treatment process is mainly borrowed from the waste recovery processes of lithium cobalt oxide, nickel cobalt manganese oxide, etc. The Chinese patent publication number is CN106450547A, and its name is a method for recovering iron phosphate and lithium carbonate from lithium iron phosphate waste. It adopts the process of oxidative roasting-phosphoric acid leaching-liquid-solid separation-precipitation of lithium carbonate to achieve the separation of lithium and phosphorus iron, and the effect is good, but the recovery of phosphorus resources is not considered, and the amount of acid and alkali used is too large, the energy consumption is large, the process is long, and the cost is very high. The wet process for recovering lithium still does not describe the recovery of phosphorus resources. Although the solid phase process for regenerating lithium iron phosphate can obtain new lithium iron phosphate positive electrode materials, it is not applicable to all battery recycled raw materials, but can only select and utilize a small part of the raw materials, and the performance of the obtained materials is still not guaranteed.

[0004] The Chinese patent publication number is CN109811125A, and the name is a method for recovering phosphorus-iron alloy and lithium compounds from waste lithium iron phosphate materials, which includes the following steps: mixing and stirring waste lithium iron phosphate materials and excess alkali metal hydroxide solution, filtering and drying the material after aluminum removal to obtain lithium iron phosphate powder; introducing reducing gas, heating for reduction treatment, and converting lithium iron phosphate into phosphorus-iron alloy and lithium compounds after decomposition; and obtaining purified phosphorus-iron alloy and lithium compounds through magnetic separation. Although the recovery process is short, it consumes a lot of energy and has a low recovery rate. The recovered phosphorus-iron alloy and lithium compounds need further separation and synthesis before they can be used, and the recovery technology is not perfect.

[0005] The Chinese patent publication number CN112811404A is a method for recycling waste lithium iron phosphate positive electrode powder. The lithium iron phosphate positive electrode powder is mixed with a first inorganic acid, a metal complexing agent and water to remove aluminum; the lithium iron phosphate material after aluminum removal is reacted with a second inorganic acid and hydrogen peroxide, filtered to obtain an iron-phosphorus filter residue; then the iron-phosphorus filter residue is dissolved with a third inorganic acid, filtered to obtain an iron-phosphorus filtrate; finally, the filtrate is precipitated and recovered by adjusting the pH value of the filtrate with an alkali to obtain iron phosphate. This method focuses on the recovery of iron phosphate, without considering the recovery of lithium and the method is complicated, which cannot meet the requirements of large-scale industrial production.

[0006] The shortcomings and deficiencies of the above existing technologies are that the recycling of iron phosphate either has very high requirements for raw materials and a narrow selection range, and can only choose to recycle iron phosphate of a part of the raw materials, while most of the raw materials on the market cannot be effectively utilized; or the cost is very high and cannot be promoted. Summary of the invention

[0007] In order to overcome the above problems, the purpose of the present invention is to provide a method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate, while recovering lithium from waste lithium iron phosphate batteries, and comprehensively utilizing phosphorus in the form of phosphate fertilizer to achieve comprehensive recycling of resources.

[0008] In order to achieve the above purpose, the technical solution adopted by the present invention is: a method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate, comprising the following steps:

[0009] Step a, mixing waste lithium iron phosphate powder and water in a certain ratio into a slurry, adding concentrated sulfuric acid and hydrogen peroxide to the slurry for oxidation, stirring for several hours, and separating and filtering out the iron phosphate slag;

[0010] Step b, removing free water and crystal water from the iron phosphate slag in step a at 320-630° C.;

[0011] Step c, pulping the purified alkali to obtain alkali solution;

[0012] Step d, fully mixing the iron phosphate slag from which free water and crystal water are removed in step b with the alkali solution in step c to obtain a mixture;

[0013] Step e: stirring the mixture in step d for a certain period of time;

[0014] Step f: heating the mixture stirred in step e;

[0015] Step g: taking samples and detecting the contents of available phosphorus and water-soluble phosphorus respectively;

[0016] Step h: adding sulfuric acid to the reactants that have passed the tests for available phosphorus and water-soluble phosphorus by spraying to adjust the pH value;

[0017] Step i: drying and dehydrating the reactants in step h to obtain a material;

[0018] Step j: adding a certain amount of adhesive to the material in step i and mixing them evenly to obtain powdered fertilizer;

[0019] Step k: If the fertilizer is made into granular form, the powdered fertilizer is granulated and then packaged, or the powdered fertilizer is directly packaged.

[0020] Preferably, in step d, the soda ash and the ferrous phosphate slag from which free water and crystal water have been removed are added in a mass ratio of 15.5% to 63.5%.

[0021] Preferably, the continuous stirring time of the mixture in step e is 0.5-5.5 hours.

[0022] Preferably, the heating temperature of the mixture in step f is 550-930° C. to allow the soda ash to react as completely as possible.

[0023] Preferably, the pH value in step h is adjusted to 7-9.

[0024] Preferably, in step i, the moisture content is controlled at 4-15% when the reactants are dried and dehydrated.

[0025] Preferably, the amount of the adhesive added in step j accounts for 0.5%-5.5% of the total material mass.

[0026] Preferably, the adhesive is one of silicate, aluminate or borate, or one of potassium ion salt, calcium ion salt and silicate ion salt.

[0027] The beneficial effects of the present invention are as follows: the method has a short flow, is simple and efficient, and has strong universality, and is suitable for large-scale industrial recovery of phosphorus sources from waste lithium iron phosphate batteries to prepare fertilizers; not only does soda ash react with iron phosphate slag to convert insoluble iron phosphate into soluble sodium phosphate, but also the acidic property of sulfuric acid is used to neutralize the unreacted soda ash in the material and adjust its pH value so as not to cause harm to the soil and crops; it also solves the problem of iron phosphate slag after lithium extraction from waste lithium iron phosphate, converts the iron phosphate slag into fertilizer that can be absorbed by crops, turns waste into treasure, reduces environmental pollution, and brings benefits to the enterprise. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a flowchart of this embodiment;

[0029] Figure 2 This is a comparison diagram of heating temperatures in the experiment of this embodiment;

[0030] Figure 3 It is a comparison chart of the amount of soda added in the experiment of this embodiment;

[0031] Figure 4 It is a comparison chart of the amount of water added in the experiment of this embodiment;

[0032] Figure 5 It is a comparison chart of heating time in the experiment of this embodiment. DETAILED DESCRIPTION

[0033] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0034] See also Figure 1 As shown, this embodiment discloses a method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate, comprising the following steps:

[0035] Step a, mixing waste lithium iron phosphate powder and water in a certain ratio into a slurry, adding concentrated sulfuric acid and hydrogen peroxide to the slurry for oxidation, stirring for several hours, and separating and filtering out the iron phosphate slag;

[0036] Step b, removing free water and crystal water from the iron phosphate slag in step a at 320-630° C.;

[0037] Step c, pulping the purified alkali to obtain alkali solution;

[0038] Step d, fully mixing the iron phosphate slag from which free water and crystallization water are removed in step b with the alkali solution in step c to obtain a mixture, wherein the soda ash and the iron phosphate slag from which free water and crystallization water are removed are added in a mass ratio of 15.5% to 63.5%;

[0039] Step e: stirring the mixture in step d for 0.5-5.5 hours;

[0040] Step f: heating the mixture stirred in step e at a temperature of 550-930° C. to allow the soda ash to react as completely as possible;

[0041] Step g: taking samples and detecting the contents of available phosphorus and water-soluble phosphorus respectively;

[0042] Step h: adding sulfuric acid to the reactants that have passed the tests for available phosphorus and water-soluble phosphorus by spraying to adjust the pH value;

[0043] Step i: drying and dehydrating the reactants in step h, controlling the moisture content to 4-15%, to obtain a material;

[0044] Step j: adding a certain amount of adhesive to the material in step i and mixing them evenly to obtain powdered fertilizer, wherein the amount of the adhesive added accounts for 0.5%-5.5% of the total material mass, and the adhesive is one of silicate, aluminate or borate, or one of potassium acid ion salt, calcium acid ion salt and silicate ion salt;

[0045] Step k: If the fertilizer is made into granular form, the powdered fertilizer is granulated and then packaged, or the powdered fertilizer is directly packaged.

[0046] The experimental data obtained according to the above method are as follows:

[0047] Experiment 1: The ferric phosphate slag was mixed with soda ash and water in a ratio of 1:0.3:0.5 to form a slurry, and dissolved at room temperature for 1 hour; after heating at 200°C for 1 hour, the content of effective phosphorus in the obtained material was 18.73%, and the content of water-soluble phosphorus was 2.73%.

[0048] Experiment 2: The ferric phosphate slag was mixed with soda ash and water in a ratio of 1:0.3:0.5 to form a slurry, and dissolved at room temperature for 1 hour; after heating at 300°C for 1 hour, the obtained material had an effective phosphorus content of 18.96% and a water-soluble phosphorus content of 4.55%.

[0049] Experiment 3: The ferric phosphate slag was mixed with soda ash and water in a ratio of 1:0.3:0.5 to form a slurry, and dissolved at room temperature for 1 hour; heated at 400°C for 1 hour, the obtained material had an effective phosphorus content of 19.24% and a water-soluble phosphorus content of 5.01%.

[0050] Experiment 4: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.3:0.5 into a slurry, dissolve it at room temperature for 1 hour; heat it at 500°C for 1 hour, and the obtained material has an effective phosphorus content of 20.21% and a water-soluble phosphorus content of 7.50%.

[0051] Experiment 5: The ferric phosphate slag was mixed with soda ash and water in a ratio of 1:0.3:0.5 to form a slurry, and dissolved at room temperature for 1 hour; heated at 600°C for 1 hour, the obtained material had an effective phosphorus content of 20.44% and a water-soluble phosphorus content of 9.60%.

[0052] Experiment 6: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.3:0.5 into a slurry, dissolve it at room temperature for 1 hour; heat it at 700°C for 1 hour, and the obtained material has an effective phosphorus content of 20.56% and a water-soluble phosphorus content of 9.72%.

[0053] Experiment seven: iron phosphate slag was mixed with soda ash and water in a ratio of 1:0.3:0.5 to form a slurry, dissolved at room temperature for 1 hour; heated at 800°C for 1 hour, the obtained material had an effective phosphorus content of 20.71% and a water-soluble phosphorus content of 9.79%.

[0054] According to the above experimental results, the effective phosphorus content and water-soluble phosphorus content of the material obtained at a heating temperature of 600℃ have reached the ideal value, so the heating temperature is selected to be 600℃, see Figure 2 Comparison chart of heating temperatures in the experiment.

[0055] Experiment 8: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.35:0.5 into a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 22.38% and a water-soluble phosphorus content of 12.51%.

[0056] Experiment 9: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.4:0.5 into a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 22.15% and a water-soluble phosphorus content of 15.22%.

[0057] Experiment 10: Mix ferrous phosphate slag, soda ash and water in a ratio of 1:0.45:0.5 into a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 23.38% and a water-soluble phosphorus content of 15.56%.

[0058] Experiment 8: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.35:0.5 into a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 22.38% and a water-soluble phosphorus content of 12.51%.

[0059] Experiment 11: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.5:0.5 to form a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 23.58% and a water-soluble phosphorus content of 15.75%.

[0060] Experiment 12: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.55:0.5 to form a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 23.65% and a water-soluble phosphorus content of 15.90%.

[0061] According to the above experimental results, the content of available phosphorus and water-soluble phosphorus in the material obtained by adding 40% soda ash, that is, the ratio of iron phosphate slag to soda ash and water is 1:0.4:0.5, has reached the ideal value. The soda ash addition amount is selected to be 40%, that is, the ratio of iron phosphate slag to soda ash is 1:0.4, see Figure 3 Comparison chart of the amount of soda ash added in the experiment.

[0062] Experiment 13: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.4:1 to form a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 23.54% and a water-soluble phosphorus content of 14.86%.

[0063] Experiment 14: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.4:0.4 to form a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 22.15% and a water-soluble phosphorus content of 15.22%.

[0064] Experiment 15: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.4:0.3 into a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 22.10% and a water-soluble phosphorus content of 14.45%.

[0065] Experiment 16: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.4:0.2 into a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 22.36% and a water-soluble phosphorus content of 14.39%.

[0066] Experiment 17: Mix ferric phosphate slag, soda ash and water in a ratio of 1:0.4:1 to form a slurry, dissolve it at room temperature for 1 hour; heat it at 600°C for 1 hour, and the obtained material has an effective phosphorus content of 22.22% and a water-soluble phosphorus content of 14.19%.

[0067] According to the above experimental results, the amount of water added has little effect on the content of available phosphorus and water-soluble phosphorus in the obtained material. Adding more water will increase energy consumption. Figure 4 Comparison chart of the amount of water added in the experiment.

[0068] Experiment 18: Mix iron phosphate slag and soda ash in a ratio of 1:0.4 and heat at 600°C for 1 hour. The obtained material has an effective phosphorus content of 22.56% and a water-soluble phosphorus content of 14.85%.

[0069] Experiment 19: Mix iron phosphate slag and soda ash in a ratio of 1:0.4, heat at 600°C for 0.5 hour, and the obtained material has an effective phosphorus content of 22.31% and a water-soluble phosphorus content of 14.12%.

[0070] Experiment 20: Mix iron phosphate slag and soda ash in a ratio of 1:0.4 and heat at 600°C for 1.5 hours. The obtained material has an effective phosphorus content of 23.39% and a water-soluble phosphorus content of 15.18%.

[0071] Experiment 21: Mix iron phosphate slag and soda ash in a ratio of 1:0.4 and heat at 600℃ for 2 hours. The obtained material has an effective phosphorus content of 23.71% and a water-soluble phosphorus content of 16.76%.

[0072] Experiment 22: Mix iron phosphate slag and soda ash in a ratio of 1:0.4 and heat at 600°C for 2.5 hours. The obtained material has an effective phosphorus content of 23.85% and a water-soluble phosphorus content of 16.59%.

[0073] Experiment 23: Mix iron phosphate slag and soda ash in a ratio of 1:0.4 and heat at 600°C for 3 hours. The obtained material has an effective phosphorus content of 23.69% and a water-soluble phosphorus content of 16.79%.

[0074] According to the above experimental results, the heating time has a great influence on the content of available phosphorus and water-soluble phosphorus in the obtained material. The longer the time, the more complete the reaction. However, when the heating time exceeds 2 hours, the content of available phosphorus and water-soluble phosphorus in the obtained material does not change much. Figure 5 Comparison chart of heating time in the experiment.

[0075] In summary, the best reaction conditions are: heating temperature of 600°C, soda ash addition of 40%, that is, the ratio of iron phosphate slag to soda ash is 1:0.4, and heating time is 2 hours.

[0076] Case 1:

[0077] 1. Material collection and pretreatment

[0078] First, waste lithium iron phosphate batteries are collected from various channels, disassembled and separated, and the iron phosphate component is extracted.

[0079] 2. Dehydration: Remove free water and crystal water from the iron phosphate slag separated and filtered after lithium extraction at 320-630℃;

[0080] 3. Crush and grind the dehydrated iron phosphate to make its particle size more uniform for subsequent chemical reactions.

[0081] 4. Conversion process

[0082] Alkali dissolution reaction: the crushed iron phosphate slag is mixed with soda ash and water in a ratio of 1:0.3:0.5 to form a slurry, dissolved at room temperature for 1 hour; heated in a rotary kiln at 600°C for 1 hour.

[0083] The reaction formula is:

[0084] Na 2 CO 3 +H 2 O→2NaOH+CO 2

[0085] FePO 4 +3NaOH→Fe(OH) 3 +Na 3 PO 4

[0086] 2Fe(OH) 3 →Fe 2 O 3 +3H 2 O

[0087] 5. Fertilizer preparation and testing

[0088] After the rotary kiln is heated, the material is discharged, cooled and sampled.

[0089] Quality testing: The quality of the prepared fertilizer is tested, including indicators such as nutrient content, pH, heavy metal content, etc. The test results show that the fertilizer meets the relevant national standards and can be safely used in agricultural production.

[0090] The material tested had an effective phosphorus content of 20.44%, a water-soluble phosphorus content of 9.60%, a pH value of 9, and a heavy metal content that was acceptable.

[0091] Formula adjustment: According to the needs of different crops, the formula of sodium phosphate fertilizer is adjusted by adding appropriate amounts of nitrogen, potassium and other elements to improve the comprehensive fertilizer efficiency.

[0092] Granulation and packaging: The adjusted sodium phosphate fertilizer is granulated to make it easy to use and store. Then it is packaged and labeled with product information and usage instructions.

[0093] Fertilizer efficiency testing and application

[0094] Laboratory test: In the laboratory, different kinds of plant seeds were selected and cultured in a culture medium containing the sodium phosphate fertilizer to observe the growth and physiological indicators of the plants. The test results show that the fertilizer can effectively promote plant growth and improve plant resistance.

[0095] Field test: Field test was conducted in actual farmland. Different plots were selected to plant the same crops. Sodium phosphate fertilizer and traditional fertilizer were applied respectively to compare their growth, yield and quality. After one growth cycle, it was found that the plots where sodium phosphate fertilizer was applied had significantly improved crop yield and quality.

[0096] Case summary

[0097] This case demonstrates the feasibility and effectiveness of converting iron phosphate into sodium phosphate as fertilizer. By recycling waste lithium iron phosphate batteries, it not only reduces resource waste and environmental pollution, but also provides a new source of fertilizer for agricultural production. At the same time, this case also provides a new development idea for other related companies, promoting resource recycling and sustainable development.

[0098] Case 2:

[0099] 1. Material collection and pretreatment

[0100] The raw materials in this case are basically the same as those in Case 1. The waste lithium iron phosphate batteries are disassembled and separated to extract the iron phosphate component.

[0101] Dehydration: Remove free water and crystal water from the iron phosphate slag separated and filtered out after lithium extraction at 320-630℃;

[0102] The dehydrated iron phosphate is crushed and ground to make its particle size more uniform for subsequent chemical reactions.

[0103] Iron phosphate slag and soda ash are mixed in a ratio of 1:0.4;

[0104] 5. Heat at 600°C for 2 hours.

[0105] The reaction formula is:

[0106] 2FePO 4 +3Na 2 CO 3 →Fe 2 (CO 3 ) 3 +2Na 3 PO 4

[0107] Fe 2 (CO 3 ) 3 →Fe 2 O 3 +3CO 2

[0108] Overall reaction formula:

[0109] 2FePO 4 +3Na 2 CO 3 →Fe 2 O 3 +3CO 2 +2Na 3 PO 4

[0110] 5. Fertilizer preparation and testing

[0111] After the rotary kiln is heated, the material is discharged, cooled and sampled.

[0112] Quality testing: The quality of the prepared fertilizer is tested, including indicators such as nutrient content, pH, heavy metal content, etc. The test results show that the fertilizer meets the relevant national standards and can be safely used in agricultural production.

[0113] The material tested had an effective phosphorus content of 23.71%, a water-soluble phosphorus content of 16.76%, a pH value of 9, and a qualified heavy metal content.

[0114] Formula adjustment: According to the needs of different crops, the formula of sodium phosphate fertilizer is adjusted by adding appropriate amounts of nitrogen, potassium and other elements to improve the comprehensive fertilizer efficiency.

[0115] Granulation and packaging: The adjusted sodium phosphate fertilizer is granulated to make it easy to use and store. Then it is packaged and labeled with product information and usage instructions.

[0116] Fertilizer efficiency testing and application

[0117] Laboratory test: In the laboratory, different kinds of plant seeds were selected and cultured in a culture medium containing the sodium phosphate fertilizer to observe the growth and physiological indicators of the plants. The test results show that the fertilizer can effectively promote plant growth and improve plant resistance.

[0118] Field test: Field test was conducted in actual farmland. Different plots were selected to plant the same crops. Sodium phosphate fertilizer and traditional fertilizer were applied respectively to compare their growth, yield and quality. After one growth cycle, it was found that the plots where sodium phosphate fertilizer was applied had significantly improved crop yield and quality.

[0119] Case summary

[0120] This case demonstrates the feasibility and effectiveness of converting iron phosphate into sodium phosphate as fertilizer. By recycling waste lithium iron phosphate batteries, it not only reduces resource waste and environmental pollution, but also provides a new source of fertilizer for agricultural production. At the same time, this case also provides a new development idea for other related companies, promoting resource recycling and sustainable development.

[0121] In the above two cases, the iron phosphate slag produced by wet extraction of lithium carbonate from waste battery recycling was tested to be free of heavy metals and no ingredients harmful to soil and crops. The iron phosphate contained about 30% free water and 20% crystal water. The treatment methods were:

[0122] After the by-product iron phosphate is dehydrated, it is mixed with the pulped soda ash solution and enters the rotary kiln for reaction.

[0123] The by-product iron phosphate is not dehydrated but directly mixed with soda ash and enters the rotary kiln, where dehydration and reaction proceed simultaneously.

[0124] In both cases, iron phosphate can be activated and converted into sodium phosphate. The test results show that the fertilizer meets the relevant national standards and can be safely used in agricultural production. The fertilizer contains iron oxide, which can also provide trace iron elements for crops. The latest research has found that iron oxide can also decompose natural organic phosphorus in the soil, including DNA, RNA, etc., which can effectively increase the sustained effect and is beneficial without harm.

[0125] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate, characterized in that: The following steps are involved: Step a, mixing waste lithium iron phosphate powder and water in a certain ratio into a slurry, adding concentrated sulfuric acid and hydrogen peroxide to the slurry for oxidation, stirring for several hours, and separating and filtering out the iron phosphate slag; Step b, removing free water and crystal water from the iron phosphate slag in step a at 320-630° C.; Step c, slurrying the purified alkali to obtain alkali solution; Step d, fully mixing the iron phosphate slag from which free water and crystal water are removed in step b with the alkali solution in step c to obtain a mixture; Step e: stirring the mixture in step d for a certain period of time; Step f: heating the mixture stirred in step e; Step g: taking samples and detecting the contents of available phosphorus and water-soluble phosphorus respectively; Step h: adding sulfuric acid to the reactants that have passed the available phosphorus and water-soluble phosphorus tests by spraying to adjust the pH value; Step i: drying and dehydrating the reactants in step h to obtain a material; Step j: adding a certain amount of adhesive to the material in step i and mixing them evenly to obtain powdered fertilizer; Step k: If the fertilizer is made into granular form, the powdered fertilizer is granulated and then packaged, or the powdered fertilizer is directly packaged.

2. The method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate according to claim 1, characterized in that: In the step d, the soda ash and the ferrous phosphate slag from which free water and crystal water have been removed are added in a mass ratio of 15.5% to 63.5%.

3. The method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate according to claim 1, characterized in that: The continuous stirring time of the mixture in step e is 0.5-5.5 hours.

4. The method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate according to claim 1, characterized in that: In step f, the mixture is heated to a temperature of 550-930° C. to allow the soda ash to react as completely as possible.

5. The method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate according to claim 1, characterized in that: In the step h, the pH value is adjusted to 7-9.

6. The method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate according to claim 1, characterized in that: In the step i, the moisture content is controlled at 4-15% when the reactants are dried and dehydrated.

7. The method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate according to claim 1, characterized in that: The amount of the adhesive added in step j accounts for 0.5%-5.5% of the total material mass.

8. The method for preparing phosphate fertilizer from iron phosphate slag after lithium extraction from waste lithium iron phosphate according to claim 7, characterized in that: The adhesive is one of silicate, aluminate or borate, or one of potassium ion salt, calcium ion salt and silicate ion salt.

Citation Information

Patent Citations

  • Method for recycling iron phosphate and lithium carbonate from lithium iron phosphate waste

    CN106450547A

  • Method for recovering phosphor iron alloy and lithium compound from waste lithium iron phosphate material

    CN109811125A

  • Recycling method of waste lithium iron phosphate positive electrode powder

    CN112811404A